2015
DOI: 10.1093/fampra/cmv076
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of persistent frequent attenders in primary care: case–control study

Abstract: Background: Most frequent attendance in primary care is temporary, but persistent frequent attendance is expensive and may be suitable for psychological intervention. To plan appropriate intervention and service delivery, there is a need for research involving standardised psychiatric interviews with assessment of physical health and health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 17 publications
6
69
2
1
Order By: Relevance
“…or a person with 30 consultations or more within a 2‐year period (Patel et al . ). In the literature, factors associated with frequent use of healthcare services have been examined (Bergh et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…or a person with 30 consultations or more within a 2‐year period (Patel et al . ). In the literature, factors associated with frequent use of healthcare services have been examined (Bergh et al .…”
Section: Introductionmentioning
confidence: 97%
“…Patel et al . ). The few studies conducted from a patient perspective have shown that frequent attenders of primary healthcare services describe a situation where they feel mistrusted and rejected by healthcare providers (Neal et al .…”
Section: Introductionmentioning
confidence: 97%
“…31,32 The factors mentioned in studies as lowering utilisation thresholds partly overlap with the characteristics of frequent attenders in primary care. 33 Although the problem of frequent attenders is usually framed as a burden for individual practices and the healthcare system, 34 the reflections of the GPs in this study shed a positive light on the phenomenon. The variability in patients' utilisation patterns allows for conclusions regarding the probability of serious illness.…”
Section: Comparison With Existing Literaturementioning
confidence: 81%
“…These effects have taken their toll, and indeed the new frontier in the battle against mental health stigma has shifted substantially to the issue of access. Due to a significant paucity in their education and training, primary care physicians feel underprepared to diagnose and treat much of the mental health problems for which they are asked to take responsibility [19]. Moreover, there is a national shortage of psychiatrists, especially in subspecialties such as geriatric, child, and addiction psychiatry.…”
Section: Current Advancesmentioning
confidence: 99%